Microtubule organization in presynaptic boutons relies on the formin DAAM. - Migh, E.; Götz, T.; Földi, I.; Szikora, S.; Gombos, R.; Darula, Z.; Medzihradszky, K.F.; Maléth, J.; Hegyi, P.; Sigrist, S.; Mihály, J. (Development, 2018)
Regulation of the cytoskeleton is fundamental to the development and function of synaptic terminals, such as neuromuscular junctions. Despite the identification of numerous proteins that regulate synaptic actin and microtubule dynamics, the mechanisms of cytoskeletal control during terminal arbor formation have remained largely elusive. Here, we show that DAAM, a member of the formin family of cytoskeleton organizing factors, is an important presynaptic regulator of neuromuscular junction development in Drosophila We demonstrate that the actin filament assembly activity of DAAM plays a negligible role in terminal formation; rather, DAAM is necessary for synaptic microtubule organization. Genetic interaction studies consistently link DAAM with the Wg/Ank2/Futsch module of microtubule regulation and bouton formation. Finally, we provide evidence that DAAM is tightly associated with the synaptic active zone scaffold, and electrophysiological data point to a role in the modulation of synaptic vesicle release. Based on these results, we propose that DAAM is an important cytoskeletal effector element of the Wg/Ank2 pathway involved in the determination of basic synaptic structures, and, additionally, that DAAM may couple the active zone scaffold to the presynaptic cytoskeleton.